Evaluation of organizational readiness in information systems adoption: a case study - Maryati Mohd Yusof; Kamisah Abd Aziz (Penerbit Universiti Kebangsaan Malaysia, 2015)
Most ICT projects failed due to various factors including organizational issues and leaders who did not sufficiently assess organizational readiness for change. Although various perspectives and criteria have been used by researchers to measure organizational readiness, reported evidence on its measurement in information systems (IS) adoption is still limited and unclear, which calls for clarification and further studies. The purpose of the paper is to discuss the evaluation of IS adoption in organizational readiness using an extended organizational readiness framework and to identify the factors that influence organizational readiness in IS adoption. A case study was conducted on the Human Resource Management Information System (HRMIS) based on the Framework of Organizational Readiness at the Public Service Department (PSD) of Malaysia. This qualitative study involved interviews, observations and document analysis. The study found that the PSD is set to implement the HRMIS but the issues and problems identified as pertaining to the HRMIS must be addressed and dealt with immediately in order to achieve the system objectives. A number of factors influencing organizational readiness were identified in the adoption of the HRMIS: Attributes of the Change (vision clarity, change appropriateness and change efficacy), Leadership Support (top management support, presence of an effective champion, and IT support), Internal Context (organizational history of change, organizational conflicts and policies, and organizational flexibility) and Attributes of the Change Targets (collective self-efficacy and user training). Although our case study focused on a specific setting, the identified factors and proposed framework extension is potentially useful for assessing other information systems in different settings; the findings could act as a guide for assessing organizational readiness prior to the adoption of information systems.